COLLECTION DEVELOPMENT STRATEGIES IN LIBRARIES - Sentiana, Fegi; Zulaikha, Sri Rohyanti; Iqbal, Rahmat; Mustofa, Muhamad Bisri; Zahro, Faizafati Matus (Jurnal El-Pustaka, 2025)
In the current information age, library materials and human life planning are characterized by the cooperation of collection resources, the development and dissemination of information, and the collection and weeding of extremely fast, precise and accurate information. In order to meet the continuous information needs of society and libraries, library managers, like the organization, must perform these stages. The collection in an information institution (library) is very important, and the success of its implementation is quite influenced by it. Conversely, the presence of a library collection is an important component that affects whether the library is well utilized by the users or not. The purpose of this study was to determine the collection development strategy in the library of Madrasah ibtidaiyah Swasta Mathla'ul Anwar. The method used in this research is descriptive qualitative method. The results of the study show that the Mathla'ul Anwar Private Madrasah Ibtidaiyah (MIS) Library has several challenges in managing the collection because there is no written policy that regulates the selection and evaluation process of the collection in a structured manner. Although selection and evaluation activities are still carried out, the uncertainty of procedures and implementation time causes the process to be less effective and inconsistent. Keywords: development strategy, collection, library.